2011
DOI: 10.1080/10473289.2011.608622
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Emissions from a Stationary Engine Fueled with Ultra-Low-Sulfur Diesel and Waste-Cooking-Oil-Derived Biodiesel

Abstract: Stationary diesel engines, especially diesel generators, are increasingly being used in both developing countries and developed countries because of increased power demand. Emissions from such engines can have adverse effects on the environment and public health. In this study, particulate emissions from a domestic stationary diesel generator running on ultra-low-sulfur diesel (ULSD) and biodiesel derived from waste cooking oil were characterized for different load conditions. Results indicated a reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Gangwar et al (2012) found that B20 PM (biodiesel from karanja oil) contained higher concentrations of Fe, Mn, and Cr, whereas the Cu concentration in diesel PM was higher. Betha and Balasubramanian (2011) determined that Zn, Cr, Cu, Fe, and Ni concentrations were higher in B100 PM (waste grease derived biodiesel). The current study suggests the importance of fuel sources and the biodiesel feedstock to metals (versus contributions from engine wear).…”
Section: Metals Resultsmentioning
confidence: 99%
“…Gangwar et al (2012) found that B20 PM (biodiesel from karanja oil) contained higher concentrations of Fe, Mn, and Cr, whereas the Cu concentration in diesel PM was higher. Betha and Balasubramanian (2011) determined that Zn, Cr, Cu, Fe, and Ni concentrations were higher in B100 PM (waste grease derived biodiesel). The current study suggests the importance of fuel sources and the biodiesel feedstock to metals (versus contributions from engine wear).…”
Section: Metals Resultsmentioning
confidence: 99%
“…However, it is to be noted that in this study the carcinogenic risk due to particulate bound elements was used as a measure to evaluate the total carcinogenic risk. A more comprehensive and extensive research needs to be done to evaluate the complete risk assessment including many other carcinogenic compounds such as In the case of PAHs the the risk assessment for PAHs that are probable and possible human carcinogens were calculated using petency equivalency factor (PEF) relative to BaP and the CDI calculated from Eq (7). Table 5 shows the PAHs with know PEFs (Collins et al, 1998 Carcinogenic risk due to individual PAHs is calculated as product of CDI and PEF.…”
Section: Elcr = CDI X Sfmentioning
confidence: 99%
“…Particle size distributions of emissions at different loads for ULSD, B50, WCOB (B100)(Betha et al, 2011a) …”
mentioning
confidence: 99%
“…They suggested that WCO biodiesel and pentanol blends can be regarded as an acceptable alternative fuel for diesel engines due to their improved combustion performance and reduced particulate emissions. Betha et al [11] studied particulate emissions from a domestic stationary diesel generator running on ultralow sulphur diesel and WCO biodiesel under different load conditions. Their results showed a decrease in particulate mass and number emissions when the fuel was switched from diesel to WCO biodiesel.…”
Section: Introductionmentioning
confidence: 99%